Hypoxia, vascular smooth muscles and endothelium - Calvin K. Chan; Paul M. Vanhoutte (Elsevier, 2013)
Hypoxia, or the lack of oxygen, has multiple impacts on the vascular system. The major molecular sensors for hypoxia at the cellular level are hypoxia inducible factor and heme oxygenase. Hypoxia also acts on the vasculature directly conveying its damaging effects through disruption of the control of vascular tone, particularly in the coronary circulation, enhancement of inflammatory responses and activation of coagulation pathways. These effects could be particularly detrimental under pathological conditions such as obstructive sleep apnea and other breathing disorders.